(untitled) (SOUTH ARAL SEA MEDICAL JOURNAL, 2025)
Pathological bone fracture is a violation of the integrity of bone tissue, which becomes brittle as a result of a disease (for example, osteoporosis, bone tuberculosis, tumor, osteomyelitis, and other pathological conditions) and is unable to withstand normal mechanical loads or minimal external influences. Unlike traumatic fractures, it occurs without strong mechanical impact on healthy bone. This article is devoted to the morphological features of pathological bone fractures, their classification and their clinical significance.